Compound Identification and Anticancer Activity of Ethyl Acetate Fraction from Bawang Sabrang (Eleutherine palmifolia (L.) Merr.) on HeLa Cervical Cancer Cell Line - Mutiah, Roihatul; Minggarwati, Trian Sidha; Kristanti, Risma Aprinda; Susanti, Erna (Indonesian Journal of Cancer Chemoprevention, 2019)
Eleutherine palmifolia (L.) Merr. is a typical plant found in Central Kalimantan that has been used empirically by the Dayak people as medicine for various diseases, including cancer. The plant contains flavonoid compounds that potentially used as an anticancer. The purpose of this study is to find the most active fraction, indicated by its cytotoxic potency on HeLa cervical cancer cell line, and to identify compounds in E. palmifolia bulbs fraction. E. palmifolia bulbs was extracted by maceration. The extraction with ultrasonic bath and partition fractionation was conducted by using n-hexane, chloroform, and ethyl acetate. Each fraction was tested for toxicity level on HeLa cells using MTT assay. The identification of active compounds was carried out by Ultra Performance Liquid Chromatography-Mass Spectrometry (UPLC-MS). The result showed that based on the IC50 value, the ethyl acetate fraction had the highest bioactivity. IC50 values of n-hexane, chloroform, and ethyl acetate fractions were 250.77±19.01; 720.46±42.38; and 44.34±9.45μg/mL, respectively. The identification of the active compound in ethyl acetate fraction resulted 28 chemical compounds. Compounds with the highest percentage area were isoliquiritigenin and oxyresveratrol. The ethyl acetate fraction of E. palmifolia bulbs is potential to be developed as an anticancer candidate (phytopharmaceutical).Keywords: Compound identification, Anticancer activity, Eleutherine palmifolia (L.) Merr., cervical cancer